The Performance of Candidates in the Examinations of the Otorhinolaryngology Specialty, Sudanese National Board of Medical Specializations - Elmustafa, Osman M; Osman, Wail N (Gezira Journal of Health Sciences; Vol 9 No 2 (2013), 2013)
Introduction: The Otorhinolaryngology, Head and Neck Surgery Council is one of the first established councils of the Sudanese National Board of Medical Specializations (SNBMS).This report covers the fourth rotation period from 2009-2013. It is meant to be in the form of an analytical study for more objectivity and transparency and to be a model for promotion of the general performance of other councils in administrative, examination and training issues. Objectives: The main objective of this study is to analyze the trainees’ results in part 1 and part 2 (final) examinations with regard to gender and pass rates and to draw relevant indices that help in planning for training and expansion of specialist services. Materials and Methods: This is an analytical retrospective study conducted at the (SNMSB) headquarters Khartoum, Sudan during the period from January 2009- December 2012 .This study covers the fourth rotation of the scientific council for the specialty. The study included all candidates sitting for both part 1 and part 2 examinations (265). Candidates were classified according to gender and pass rates. Candidates who withdrew form the program after passing the part 1 examination were excluded. Results:  The total number of doctors sitting for part 1 examinant was 207. Females were 118 and males were 89. Female to male ratio was 1.3:1.0. Sixty nine (69) doctors passed the examination with over all pass percentage of 33.3%. The percentage of passed candidates among females was 31% and among males was 36%. The total number for trainees sitting for the final examination was 58. Females were 23 and males were 35. Female to male ratio was 1.0: 1.5. Thirty three (33) trainees passed the examination with over all pass percentage of 56.9%. The percentage of passed trainees among females was 52.2% and among males was 60%. The annual number of doctors sitting for part 1 examination showed marked reduction from 69 in the first year to 48 in the fourth year although there was a steady increase in-between. The average annual pass rate for part 1 examination showed noticeable increase from 23% to 42% by the end of the fourth year. The annual number of trainees sitting for the final examination was fluctuating and the biggest number was in the first year. There was a minimal increase in the number of graduates.  Conclusions : Applicants for part one examination are mostly females. Applicants numbers are generally decreasing. The pass percentages are increasing in both parts of the examination. Males performance in both part one and part two examinations is better than females. The number of graduates does not satisfy the national needs for specialist services provision and expansion.